2004
DOI: 10.1016/j.physa.2003.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Variance fluctuations in nonstationary time series: a comparative study of music genres

Abstract: An important problem in physics concerns the analysis of audio time series generated by transduced acoustic phenomena. Here, we develop a new method to quantify the scaling properties of the local variance of nonstationary time series. We apply this technique to analyze audio signals obtained from selected genres of music. We find quantitative differences in the correlation properties of high art music, popular music, and dance music. We discuss the relevance of these objective findings in relation to the subj… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 23 publications
2
41
0
1
Order By: Relevance
“…One of the most famous and well-known approach used in many studies is Multifractal Detrended Fluctuations Analysis (MF-DFA) [51,52]. This method has been applied to various areas, such as economical time series [53-55,?,56], river flow [13] and sunspot fluctuations [57,58], cosmic microwave background radiations [59], music [60,61], plasma fluctuations [62].…”
Section: Analysis Techniques and Data Descriptionmentioning
confidence: 99%
“…One of the most famous and well-known approach used in many studies is Multifractal Detrended Fluctuations Analysis (MF-DFA) [51,52]. This method has been applied to various areas, such as economical time series [53-55,?,56], river flow [13] and sunspot fluctuations [57,58], cosmic microwave background radiations [59], music [60,61], plasma fluctuations [62].…”
Section: Analysis Techniques and Data Descriptionmentioning
confidence: 99%
“…Dagdug et al [31] investigated a specific piece of Mozart employing detrended fluctuation analysis (DFA) [32]. Applying DFA in a volatility-like series, Jennings et al [33] found quantitative differences in the Hurst exponent depending on the music genre.…”
mentioning
confidence: 99%
“…Detrended fluctuation analysis is a standard method that was developed in the context of time-series analysis to study 1/f noise and long-range correlations [37] and has proven to be very reliable particularly in dealing with nonstationary time series and trends in the data [6,37,38,44,45]. It has also been used outside the time domain, e.g., to study the organization of DNA nucleotides [39].…”
Section: B Detrended Fluctuation Analysismentioning
confidence: 99%